Permanent First Mandibular Molar: Loss Prevalence and Pattern among Saudis in Al-Ahsa - Almahdi, Hatim Mohammed; Alabdrabulridha, Zuhair; AlAbbas, Jawad; Saad, Ali Albin; Alarka, Ismail; Alghatm, Sajjad; Alqasem, Hadi (European Journal of Dentistry, 2022)
Objectives The permanent first mandibular molar (PFMM) is the first tooth to erupt, usually at the age of 6 years. It is the most effective oral masticatory unit due to its wide occlusal surface and its role in favorable occlusion. This study describes the prevalence of PFMM loss and the reasons for extraction in a group of King Faisal Dental Complex Clinics (KFUDC) Saudi attendees. In addition, to report postextraction complications, consider the gender, age, and the time elapsed from the moment of the extraction.Materials and Methods A cross-sectional study was performed in January to April 2020, focusing on the loss of PFMM among a group of Saudis attending KFUDC in Al Hofuf, Saudi Arabia. A total of 417 participants were recruited. The inclusion criteria were adults aged ≥ 18 years. The principal investigator performed all the necessary measures for calibration in the forms of training on clinical examination and interviews.Statistical Analysis Data were analyzed using the Statistical Package for the Social Science, version 25 (SPSS Inc., Illinois, United States).Result Four hundred seventeen attendees participated in the present study. Majority were males 73.9% (308), and 26.1% (109) females. A third, 30% (125), reported missing PFMM; the overwhelming majority reported the reason for extraction as caries 93.6% (117).On clinical examination, 80.8% (101) had complications; drifting of adjacent teeth was the most common complication, 57.6% (72), followed by supraeruption in 23.2% (29).More males than females reported missing PFMM (22.8 and 7.2%, respectively), and those ≥ 25 years reported more missing PFMM than younger (17.5 and 12.5%, p ≤ 0.000). Those confirmed with systemic diseases reported more missing PFMM than their counterpart (23.3 and 6.7%, p ≤ 0.01).Those with good oral hygiene reported less missing PFMM than their poor oral hygiene counterparts (27.8 and 34%). Those who had good knowledge about the complications of early extraction of PFMM stated less missing PFMM than their counterparts (15.6 and 14.4%, p ≤ 0.01).Conclusion This study indicated that PFMM were the most common extracted tooth. Caries is the principal reason for tooth extraction among the studied population, followed by periodontal diseases. Emphasis on preventing dental caries is essential to maintain a socially and economically productive life and reduce the burden of oral disease.
Keywords: caries; permanent first mandibular molar; Saudi Arabia; tooth extraction